Eynullayeva, Malahat - (:unkn) unknown (My University, 2026)
Malahat Tapdig Eynullayeva, PhD in Architecture, graduated with distinction from the Faculty of Architecture at the Azerbaijan University of Architecture and Construction, earning her Bachelor's degree in 2000 and her Master's degree in 2002. In 2011, she was awarded the degree of Doctor of Philosophy (PhD) in Architecture by the Higher Attestation Commission under the President of the Republic of Azerbaijan. Since 2002, she has been a faculty member of the Faculty of Architecture at AzUAC and currently serves as an Associate Professor in the Department of Fundamentals of Architecture. She is actively engaged in research on architectural issues, regularly participates in national and international scientific conferences, and has published numerous scholarly papers. She continues her academic and teaching activities successfully.